2018
DOI: 10.1101/310102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the effect of Target of Rapamycin kinase inhibition on theChlamydomonas reinhardtiiphosphoproteome: from known homologs to new targets

Abstract: 1• Target of Rapamycin (TOR) kinase is a conserved regulator of cell growth whose activity is 2 modulated in response to nutrients, energy and stress. Key proteins involved in the pathway 3 are conserved in the model photosynthetic microalga Chlamydomonas reinhardtii, but the 4 substrates of TOR kinase and downstream signaling network have not been elucidated. Our 5 study provides a new resource for investigating the phosphorylation networks governed by the 6 TOR kinase pathway in Chlamydomonas. 7• We used qua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…NPQ involves the dissipation of excess energy by the photosynthetic apparatus, activated during high light acclimation, change in CO 2 and stress levels via three major contributing components, namely, qE (involving pigments such as xanthophylls and other carotenoids), qT (involving state transitions), and qI (D1 core damage repair) (Erickson et al, ; Müller, Li, & Niyogi, ). Recently, it has been shown that carotenoid production is under the control of TOR kinase, thus rationalizing its role in the regulation of qE (Werth et al, ). Moreover, our study shows increase in the levels of LHCSR3 upon TOR kinase inhibition in comparison to untreated cells, which suggests that the qE component of NPQ is active (Figure e; Figure c).…”
Section: Discussionmentioning
confidence: 98%
“…NPQ involves the dissipation of excess energy by the photosynthetic apparatus, activated during high light acclimation, change in CO 2 and stress levels via three major contributing components, namely, qE (involving pigments such as xanthophylls and other carotenoids), qT (involving state transitions), and qI (D1 core damage repair) (Erickson et al, ; Müller, Li, & Niyogi, ). Recently, it has been shown that carotenoid production is under the control of TOR kinase, thus rationalizing its role in the regulation of qE (Werth et al, ). Moreover, our study shows increase in the levels of LHCSR3 upon TOR kinase inhibition in comparison to untreated cells, which suggests that the qE component of NPQ is active (Figure e; Figure c).…”
Section: Discussionmentioning
confidence: 98%